Less-Tight Versus Tight Control of Hypertension in Pregnancy. Issue 5 (May 2015) - Magee, Laura A.; von Dadelszen, Peter; Rey, Evelyne; Ross, Susan; Asztalos, Elizabeth; Murphy, Kellie E.; Menzies, Jennifer; Sanchez, Johanna; Singer, Joel; Gafni, Amiram; Gruslin, Andrée; Helewa, Michael; et al.
<x xml:space="preserve">Abstract</x> ABSTRACT Nearly 10% of pregnant women have hypertension, which can increase both perinatal and maternal risk. While there have been several randomized controlled trials examining hypertension in pregnant women, they were not consistent enough to determine blood-pressure targets for pregnant women experiencing hypertension. Current guidelines are debated over treatment goals between less-tight control (blood pressure elevated but not threatening) and tight control. The Control of Hypertension in Pregnancy Study evaluated perinatal and maternal outcomes of nonsevere hypertension in pregnancy by comparing less-tight control and tight control. This study was an open, multicenter, international, randomized controlled trial that included women with nonsevere, nonproteinuric preexisting hypertension/gestational hypertension. All women had gestational periods of 14 weeks 0 days to 33 weeks 6 days with preexisting hypertension with a diastolic blood pressure of 90 mm Hg or higher at 20 weeks. Women were randomized 1:1 to less-tight control group (100 mm Hg) or tight control group (85 mm Hg). Primary outcomes focused on pregnancy loss or need for high-level neonatal care more than 48 hours to 28 days after birth. The secondary outcomes focused on "serious" maternal complications up to 6 weeks after birth and was defined as conditions such as stroke, uncontrollable hypertension, or death. Of the women who met the criteria, 497 women were randomly assigned to the less-tight control group, and 490 were assigned to the tight control group. Results for the primary outcome were found to be similar between the 2 groups, with 31.4% for the less-tight control and 30.7% tight control (adjusted odds ratio [aOR], 1.02; 95% confidence interval, 0.77–1.35). Similarities were also found in the secondary outcomes as well with maternal complications at 3.7% and 2.0% (aOR, 1.74; 95% confidence interval, 0.79–3.84). However, results revealed that less-tight control had higher rates of severe maternal hypertension (40.6%) compared with the tight control (27.5%). In addition, there were more patients in the less-tight control group with thrombocytopenia or elevated transaminases; however, the rate of HELLP syndrome was not statistically significantly increased (aOR, 4.35; 0.93–20.35). With regard to the rate of small-for-gestational-age neonates, this was examined both at the less than the 10th percentile and less than the third percentile. For the less than the 10th percentile, the absolute percentage was lower in the less-tight control group (16.1% vs 19.7%); however, this was not statistically significant, with an aOR of 0.78 (0.56–1.08). Similarly, the less than the third percentile rates were not different with an aOR of 0.92 (0.51–1.63) when comparing the less-tight control group with the tight control group. This randomized trial revealed that there was no significant difference between less-tight control and tight control in regard to the primary perinatal or maternal outcomes examined. However, less-tight control was found to have a higher rate of severe maternal hypertension.